2018
DOI: 10.17650/1726-9784-2018-17-2-63-70
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical toxicological study of analogue of hypothalamic hormone tsifetrilin

Abstract: Результаты. В результате изучения острой токсичности на мышах и крысах-самках и самцах-при введении ЦФ в максимально возможной концентрации и максимально возможных объемах препарат не вызывал гибели животных, не оказывал влияния на общее состояние животных, не вызывал внешних проявлений токсичности, не изменял поведенческие реакции животных. При изучении хронической токсичности ЦФ на крысах и собаках при ежедневном пероральном применении в течение 15 дней во всех исследованных дозах также не наблюдалось гибели… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Non-clinical studies of Cyphetrylin tablets pharmacokinetics showed the availability of Cyphetrylin for all studied organs and tissues, including brain and tumour [79]. And the results of non-clinical safety studies allowed to determine the initial (starting) safe dose for humans for phase I clinical trials [80].…”
Section: Fig 1: Structural Formula Of Cyphetrylinmentioning
confidence: 99%
“…Non-clinical studies of Cyphetrylin tablets pharmacokinetics showed the availability of Cyphetrylin for all studied organs and tissues, including brain and tumour [79]. And the results of non-clinical safety studies allowed to determine the initial (starting) safe dose for humans for phase I clinical trials [80].…”
Section: Fig 1: Structural Formula Of Cyphetrylinmentioning
confidence: 99%
“…But cyphetrylin is insoluble in water, and it is metabolically stable in the gastric fluid because of reactive groups blocking. The specific studies of cyphetrylin in vivo showed its high antitumor efficiency on animal's experimental tumours and xenografts by oral administration [8,9].…”
Section: Introductionmentioning
confidence: 99%